Factor Xa inhibitors in clinical practice: Comparison of pharmacokinetic profiles. Issue 1 (February 2020) - Goto, Eri; Horinaka, Shigeo; Ishimitsu, Toshihiko; Kato, Toru
Abstract: Background: The anticoagulant actions of oral direct factor Xa (FXa) inhibitors can be inferred from their observed plasma concentrations; however, the steady-state pharmacokinetics (PK) of different FXa inhibitors have not been compared in clinically. Methods: The sensitivity of the rivaroxaban, apixaban, and edoxaban in the STA-Liquid Anti-FXa assay were compared, and the anti-FXa plasma concentrations were measured for PK assessments. Nonlinear mixed-effects modeling was used to assess population PK in 329 patients with nonvalvular atrial fibrillation or venous thromboembolism. Patients were followed up for an average of 3.6 years. Results: Sensitivity was similar among the three drugs in this assay, which could directly compare plasma concentrations instead of anti-FXa activities. Overall exposure was greatest in 5 mg BID apixaban relative to other drugs (p < 0.001). The geometric mean AUC for the 0 to 24-h interval was 4550 ng h/mL for apixaban, 2710 ng h/mL for 15 mg QD rivaroxaban, and 1290 ng h/mL for 60 mg QD edoxaban. The PKs of 2.5 mg BID apixaban or 15 mg QD rivaroxaban were associated with hemorrhagic events. Conclusions: Apixaban was associated with greater exposure, higher trough concentrations in plasma compared with rivaroxaban or edoxaban. Furthermore, a higher plasma concentration may partially predict hemorrhagic events. Graphical abstract: Image 1